The Chapman Center Rural Crime Map Project: Kansas Crime, 1890 - 1930 - Morgan, M.J.; Adam, Janet; Peters, Grant; Hall, Rebecca; Schnee, Angela (Kansas State University, The Chapman Center for Rural Studies, 2013)
During four semesters of the academic years 2011-2013, Chapman Center students conducted research into rural crime occurring in (mainly) the service area of Chapman Center for Rural Studies, a ten-county area surrounding Manhattan, Kansas. Students worked with two groups of newspapers published predominantly between 1890 and 1930, selecting crimes reported in enough detail to drive analysis. The newspapers students most consistently consulted were The Westmoreland Recorder, The Manhattan Nationalist, The Manhattan Mercury, and The Junction City Sentinel and Tribune. In a more urban setting was The Wichita Eagle. However populous the community, the newspapers still reported crime occurring in rural areas. Up until 1930, 43.8% of the national population still lived in rural areas, combining rural-farm and rural nonfarm (village) populations (SOURCE: U.S. Census Bureau). This percentage was even higher in agricultural states like Kansas. We chose the newspapers used to gather data based on their availability to students as either bound volumes (e.g., The Westmoreland Recorder at Rock Creek Valley Historical Society in Pottawatomie County) or digitized online through such sites such as The Library of Congress or Kansas State Historical Society. We wanted to eliminate microfilm searching, as obtaining and searching microfilm is quite time-intensive for students.